Guar—Cyamopsis tetragonoloba (L.) Taub. - James M. Stephens (EDIS)
This document provides an overview of guar (Cyamopsis tetragonoloba), a drought-resistant legume native to India, valued for its soil-enriching properties and commercial seed gum. It describes the plant’s characteristics, cultivation requirements, and uses, particularly in tropical climates like Florida. Guar is typically grown during warm seasons and is sensitive to cold. While primarily used for fodder and industrial gum, its young pods are also consumed as vegetables. The document outlines cultural practices for growing guar as a garden crop rather than for large-scale agronomic production. Original publication 1994.